A Simulation Study On Photovoltaic Thermal Nanofluid Silicon Carbide Using Computational Fluid Dynamics - Mohd Ahadlin, Mohd Ahassolehin (2020)
Hybrid collector of photovoltaic thermal solar collector (PVT) produced electricity and thermal energy simultaneously. The electricity generated can be connected to grid or be used to operate the fan or pump. This research is aimed at investigating the type of nanofluid for PVT. There are having the three concentration nanofluid SiC at 0.5 wt%, 1.0 wt% and 1.5wt%. The computational fluid dynamics (CFD) simulation was carried out by the program ANSYS Fluent. For this research, water was selected as the heat transfer fluid for the verification and validation, although at difference concentration for the analysis based on nanofluid SiC. The geometry model was drawn Design Moduler (DM) and meshing to generated mesh model. The viscous model, radiation model, and material properties have been built in system simulation, and the heat transfer flow is laminar flow. The coupled wall model was thus used in radiation model, the photovoltaic panel used in this photovoltaic cell based on silicon study. Validation was done by comparison to prior research. On the other hand, in comparison between previous research and current, the root mean square error was 9.37 per cent. The influences of velocity and solar irradiance intensity on performance PVT nanofluid were determined by using CFD simulation. The highest numbers of total efficiency are at concentration nanofluid 0.5 wt% and velocity 0.010 m/s at value 49.42%.